Polyketides isolated from an endophyte Penicillium oxalicum 2021CDF-3 inhibit pancreatic tumor growth - Weng, Wenya; Li, Ruidian; Zhang, Yanxia; Pan, Xiaofu; Jiang, Shicui; Sun, Chuchu; Zhang, Chi; Lu, Xuemian (Frontiers in Microbiology, 2022)
Fungal secondary metabolites are inherently considered as valuable resources for new drugs discovery. To search for novel fungal secondary metabolites with lead compounds potential, a fungal strain Penicillium oxalicum 2021CDF-3, an endophyte of the marine red algae Rhodomela confervoides, was chemically studied. Cultivation of this fungus on solid rice medium yielded ten structurally diverse metabolites (1−10), including two new polyketides, namely oxalichroman A (1) and oxalihexane A (2). Their structures were determined by detailed analysis of NMR and HRESIMS spectroscopic data. Oxalihexane A (2) was elucidated as a novel polyketide formed by a cyclohexane and cyclohexanone moiety via an ether bond. The stereochemistry of 2 was successfully assigned by NMR and ECD calculations. In the cytotoxic assay, the new compound 2 showed remarkable inhibitory effect on the human pancreatic cancer PATU8988T cell line. Further pharmacological study demonstrated that the expression level of Cyclin D1 was down-regulated by the treatment with 2, which suggested that cell cyclin abnormity was involved in pancreatic tumor cell apoptosis. Moreover, the activation of Wnt5a/Cyclin D1 signaling pathway might be involved in the mechanism of panreatic tumor cell apoptosis induced by 2.